Cerebrospinal fluid fistula after endoscopic transsphenoidal surgery: experience in a spanish center Fístula liquórica após cirurgia transesfenoidal endoscópica: experiência de um centro espanhol - Alicia Del Carmen Becerra Romero; Joaquim Enseñat Nora; Thomaz Eduardo Topczewski; Paulo Henrique Pires de Aguiar; Isam Alobid; Enrique Ferrer Rodriguéz (Arquivos de Neuro-Psiquiatria, 2010)
BACKGROUND: Postoperative cerebrospinal fluid (CSF) fistula is the most serious complication after transsphenoidal surgery. OBJECTIVE: To analyze the incidence of CSF fistula after endoscopic transsphenoidal surgery for tumor removal in sellar region; to discuss associated factors and methods used for sellar closure. METHOD: Retrospective study of 67 patients (73 surgeries) operated via transsphenoidal endoscopy at Hospital Vall D'Hebron and Hospital Clinic of the Universidad de Barcelona, Spain. The data collected included: age, sex, hospitalization stay, suprasellar extension of the lesion, type of tumor, evidence of intraoperative CSF fistula, complications of postoperative CSF fistula, previous surgery and radiotherapy. RESULTS: Six patients (8.2%) had postoperative CSF fistula, and their average hospitalization was 5 days longer with resulting complications: two of whom had pneumoencephalus and two with meningitis. No association was found between the data collected and postoperative CSF fistula. CONCLUSION: The rate of CSF fistula after endoscopic transsphenoidal surgery from the present study is contained within the literature. Unlike other reports, no association between the variables and postoperative CSF fistula was found in this report. A fístula liquórica pós-operatória é a complicação mais séria após cirurgia transesfenoidal. OBJETIVO: Analisar a incidência de fístula liquórica após cirurgia endoscópica transesfenoidal para remoção de tumores selares, discutir fatores associados e método utilizado para fechamento selar. MÉTODO: Estudo retrospectivo de 67 pacientes (73 cirurgias) operados via endoscopia transesfenoidal no Hospital Vall D'Hebron e Hospital Clínic da Universidad de Barcelona, Espanha. Os dados coletados foram: idade, sexo, dias de internação, extensão supra-selar da lesão, tipo de tumor, evidência de fístula liquórica intra-operatória, complicações da fístula liquórica pós-operatória, cirurgia e radioterapia prévias. RESULTADOS: Seis pacientes (8.2%) tiveram fístula liquórica pós-operatória. Nestes a média de internação hospitalar foi 5 dias maior e tendo complicações decorrentes: dois com pneumoencéfalo e dois com meningite. Não se encontrou associação entre os dados coletados e fístula liquórica pós-operatória. CONCLUSÃO: A taxa de fistula liquórica após cirurgia transesfenoidal endoscópica do presente estudo está dentro da literatura. Ao contrário de outros relatos, nesta pesquisa não foi encontrada associação entre as variáveis e fístula liquórica pós-operatória.